European Integration, Economy and Corruption in the Western Balkans - Malaj, Emi (European Journal of Economics and Business Studies, 2020)
The European Union countries and institutions have constantly contributed to the European integration process of the Western Balkan countries. Albania, Serbia, Montenegro and the Republic of North Macedonia are official candidates for EU membership. Chapters and accession negotiations have been opened with Montenegro and Serbia, whereas Kosovo and Bosnia and Herzegovina are potential candidate countries. Poverty, unemployment and corruption are probably the most common problems that Western Balkan citizens face. Corruption, in itself, does not lead to poverty, but it stimulate poverty through indirect channels by affecting economic, social, political and administrative conditions. Both, the enhancement of business climate for private investors, and a higher level of integration with the European Union will decrease unemployment and will boost economic growth. Authorities should follow concrete policies in order to encourage private sector investment, increase regional integration, and create new jobs. The future of the Western Balkans is in the European Union.